Experimental Study on Resilient Modulus of Asphalt Mixture with Fibre - Krishnan, Mohan; Mohamad Taher, Mohammad Nasir (Recent Trends in Civil Engineering and Built Environment, 2024)
Generally, in Malaysia all the road used are consists of flexible pavement and using asphalt mixture as the wearing course. However, due to heavy traffic loads effects, most of the roads are experience failure and distress such as stripping, fatigue and so on. This research is conducted to study the analysis on resilient modulus of asphalt mix with steel fibre. To perform this study, samples for each mixture based on super pave design is prepared and tested. Once design samples were complete and the optimum binder content was achieved, about eighteen (18) samples are prepared to evaluate the resilient modulus value on each sample towards the presence of percentage of steel fibre in three (3) different parameter which is (0% ,1% ,1.5% ,2% ,2.5% ,3%). Resilient modulus test was conducted to determine the sample capability in receiving the loads and under tensile strength. Data for this this research were analyzed based on test conducted. Variation on the temperature control which is 25ºC can be made to obtain more various result and widen the study perspective.